Tomato crop response to short-duration legume green manures in tropical vegetable systems - Tho¨nnissen, Carmen; Midmore, David J.; Ladha, Jagdish K.; Holmer, Robert J.; Schmidhalter, Urs (Wiley, 2000)
The potential of legume green manure (GM) as an alternative to mineral N fertilizer in tropical horticulture has received scant attention. The feasibility of meeting N needs of tomato (Lycopersicon esculentum Mill.) with GM was studied in six field experiments at three locations in major vegetable growing areas of Taiwan and the Philippines between 1993 and 1995. Legume biomass, N2 fixation and N accumulation, and tomato yield and N uptake were quantified within a 6‐mo experiment cropping pattern. Yields of GM‐amended tomato crops were compared with those amended with fertilizer N (0–150 kg N ha−1). The residual effect of the fertilizing method of a second crop (maize; Zea mays L.) was estimated at AVRDC by measures of biomass and N uptake 30 d after sowing. Legume N recovery in tomato crops was traced with 15N at Mariano Marcos State University (MMSU). Soybean [Glycine max (L.) Merr.] harvested at 60 to 74 d accumulated a minimum of 2.8 Mg ha−1 biomass and 100 kg ha−1 N in all locations and seasons. A maximum of 6 Mg biomass ha−1 and 140 kg N ha−1 was reached in the wet season (WS) at AVRDC. Indigofera (Indigofera tinctoria L.) and mungbean [Vigna radiata (L.) Wilcz.] biomass yields were more variable and always inferior than soybean yields. Tomato yields across locations ranged from 3 to 70 Mg fruit ha−1. Tomato yields responded to GM N in the WS in Taiwan and in the northern Philippines, comparing favorably with fertilizer at 38 to 120 kg N ha−1. No response to GM N was found in the dry season (DS) at AVRDC or at Bukidnon Resources Company, Inc. (BRCI). The 15N experiments showed that only a small fraction of legume N (9–15%) was recovered by the tomato crop at MMSU. Maize biomass and N uptake, following the tomato crop, was increased with soybean GM compared with the control in the AVRDC WS and DS. Tomato yield response to GM N is high on infertile soils and tomato N requirement can be substituted fully or partially by GM, depending on soil N mineralization.